Association between Paraoxonase/Arylesterase Activity of Serum PON-1 Enzyme and Rheumatoid Arthritis: A Systematic Review and Meta-Analysis - Gian Luca Erre; Stefania Bassu; Roberta Giordo; Arduino A. Mangoni; Ciriaco Carru; Gianfranco Pintus; Angelo Zinellu (MDPI AG, 2022)
Background: A decrease in serum paraoxonase (PON-1) and arylesterase (ARE) activity has been reported in rheumatoid arthritis (RA) patients and linked to chronic inflammation and impaired antioxidant defense. Methods: A systematic review and meta-analysis were performed to critically appraise the current evidence on plasma/serum concentrations of PON-1 and ARE activity in RA patients and healthy controls. The Web of Science, PubMed, Scopus, and Google Scholar databases were searched from inception to November 2021. We used random-effects meta-analysis. The risk of bias was estimated using the Joanna Briggs Institute Critical Appraisal Checklist tool. The certainty of the evidence was assessed with GRADE. The study complied with the PRISMA statements and was registered in PROSPERO (CRD42022345380). Results: Seventeen studies reported PON-1 activity (1144 RA patients, 797 controls) and ten reported ARE activity (1367 RA patients, 1037 controls). RA patients had significantly lower PON-1 (SMD = −1.32, 95% CI −1.94 to −0.70; p < 0.001) and ARE activity (SMD = −0.91, 95% CI −1.37 to −0.46; p < 0.001). There was substantial heterogeneity (PON, I2 97%; ARE, 95.7%, p < 0.001 for both). There was no publication bias. The pooled SMD values did not significantly change after sensitivity analysis. The certainty of the evidence was very low due to the observational nature of the studies and the large heterogeneity. Conclusion: Our meta-analysis has shown that both serum PON-1 and ARE activity are significantly lower in RA patients, suggesting a deficit in antioxidant defense mechanisms in this disease.